Business plan for a not-for profit organization focused in long-term unemployment - Caetano, Pedro Nuno Tomás (2013)
The main purpose of this work is to present a business plan for the creation of a not-for-profit organization focused in a social and demographic problem, the long-term unemployment. The methodology used in this work is to understand how does a not-for-profit organization work and which factors (strategy, marketing, human resources and others) are critical in order to manage one organization in the best way possible. Also a market analysis was developed in the fields of long-term unemployment in order to understand its roots and major issues and what kind of potential opportunities are available to overcome the current situation. The following step was applying tools such as PEST analysis, Porter’ 5 forces, EFE, IFE and TOWS matrix to properly understand the Portuguese market and to make a good decision in terms of positioning and target market. The organization will be built upon the definition of the strategy, its goals, its mission and vision, the marketing mix and the services that the organization intends to provide (which were built taking into consideration the market research on the unemployment). Finally, a financial analysis was developed to assess the financial capability of the organization / project, which also took into consideration the financial impact of the organization for the Portuguese state.